The effect of murrattal recitation of Qur'an Muri-Q to anxiety of pregnant in the third trimester - Iin Setiawati; Selvia Nurul Qomari; Soliha Soliha (International Journal of Health Science and Technology, 2022)
Anxiety gets worse when pregnant women experience fear of childbirth. To overcome this problem, murattal recitation of Qur'an is played, because it is effective in increasing calm. The purpose of the study was to analyze the effectiveness of the Murattal recitation of Qur'an Muri-Q method on the anxiety of pregnant women in the third trimester. The pre-experimental research design with an approach one group pretest posttest design. The research population was all 32 pregnant women, the sample size using the Slovin formula was 29.6 rounded up to 30 pregnant women, with the criteria that pregnant women did not experience hearing loss and were willing to be respondents, in PBM Meiyuni. The research instrument used the Zhung Self Rating Scale (ZCAS). The results of the study before being given the Murattal recitation of Qur'an with the Muri-Q method, almost all of the anxiety of pregnant women was mild (93%), after being given the Murattal recitation of Qur'an of the Muri-Q method, all of the anxiety of pregnant women was mild (100%) and based on statistical tests showed = 0 ,00 (ρα) which meant that Murattal recitation of Qur'an is effective in reducing the anxiety of pregnant women in the third trimester before delivery.